Handbook of Research on Teacher Education: Enduring Questions in Changing Contexts - Cochran-Smith, Marilyn; Feiman-Nemser, Sharon; McIntyre, D. John; Demers, Kelly E. (Routledge, 2008)
Co-Published by Routledge/Taylor & Francis Group and the Association of Teacher Educators. The Handbook of Research on Teacher Education was initiated to ferment change in education based on solid evidence. The publication of the First Edition was a signal event in 1990. While the preparation of educators was then – and continues to be – the topic of substantial discussion, there did not exist a codification of the best that was known at the time about teacher education. Reflecting the needs of educators today, the Third Edition takes a new approach to achieving the same purpose. Beyond simply conceptualizing the broad landscape of teacher education and providing comprehensive reviews of the latest research for major domains of practice, this edition: stimulates a broad conversation about foundational issues brings multiple perspectives to bear provides new specificity to topics that have been undifferentiated in the past includes diverse voices in the conversation. The Editors, with an Advisory Board, identified nine foundational issues and translated them into a set of focal questions: What’s the Point?: The Purposes of Teacher Education What Should Teachers Know? Teacher Capacities: Knowledge, Beliefs, Skills, and Commitments Where Should Teachers Be Taught? Settings and Roles in Teacher Education Who Teaches? Who Should Teach? Teacher Recruitment, Selection, and Retention Does Difference Make a Difference? Diversity and Teacher Education How Do People Learn to Teach? Who’s in Charge? Authority in Teacher Education How Do We Know What We Know? Research and Teacher Education What Good is Teacher Education? The Place of Teacher Education in Teachers’ Education. The Association of Teacher Educators (ATE) is an individual membership organization devoted solely to the improvement of teacher education both for school-based and post secondary teacher educators. For more information on our organization and publications, please visit: www.ate1.org
Google-Books-ID: NNSRAgAAQBAJ